Identifikasi Kegagalan Pengelasan Mesin Soudronic Ag (Mesin Welder Kaleng) Menggunakan Metode Fishbone Analysis - Wilarso .; Nandang Imam Santosa (Fakultas Teknik UMSU, 2021)
In the welding process, welding on cans for aerosol liquid fluid, mosquito repellent spray, and air freshener sometimes fails, of the 3000 pcs of cans created during testing, of which 300 pcs have leaks. This study aims to reduce the dismissal of the output of tin. Study methods using the method of fishbone analysis. From the report, it was observed that the incorrect roll profile had a significant impact on the outcomes while welding. Using roll welding with a diameter of 49 mm and a profile width of 2.10 mm, with a depth of 0.30-0.35 mm, for aerosol cans with a diameter of 65 mm. Wire wire with a diameter of 1,50 mm is used. Check the upper welding roll regularly in order not to encounter damage on the profile roll, as wear on the upper welding roll will result in welding failure. It must be removed according to the state of the components to mitigate welding defects that result in cone leakage, and after removing the upper welding roll, the welding results will be refused by 0 percent.